Teaching Speaking Skills by Using Snowball Throwing Technique to the Junior High School Students - Anwar, Aulia Nanda Sari; Manurung, Konder; Nadrun, Nadrun; Kamaruddin, Abdul (Lectura : Jurnal Pendidikan, 2025)
This study examines the effectiveness of the Snowball Throwing technique in improving the speaking skills of junior high school students. Speaking is considered a crucial aspect of English language learning, requiring students to communicate ideas clearly and confidently. Traditional methods often fail to stimulate active participation, prompting the need for more engaging approaches. The Snowball Throwing technique offers an interactive alternative that involves students writing questions on pieces of paper, crumpling them into balls, and throwing them to classmates who answer them verbally. This activity fosters spontaneous speech, peer interaction, and critical thinking. A quasi-experimental design was used with two classes: an experimental group taught using the Snowball Throwing technique and a control group taught using conventional methods. Before the treatment, the average score of the experimental group was 62.4 and the control group was 62.2. After the application of Snowball Throwing Technique, the experimental group’s post-test score increased to 82.6, while the control group only reached 68.5. The Mann-Whitney U test results showed a significance value of 0.000 (p < 0.05), which means there is a significant difference between the two groups. This technique proved to be effective in improving speaking skills, especially in the aspects of fluency, accuracy, and comprehensibility. In addition, this technique also increased students’ confidence and active participation, in line with Vygotsky’s theory that social interaction in cooperative learning accelerates language acquisition.